Federalism in the Iraqi constitution The relationship between the federal government, the region and the provinces - Ali, Firas Abdel Karim Mohamed (The International and Political Journal, 2022)
Iraq is one of the countries whose people are characterized by the many of Nationalities and sects, the diversity of their beliefs, religions, languages and dialects, and this particularity requires the experience of democratic rule that establishes a state of citizenship and law and equal employment opportunities for all members of the people. The success of the democratic experiment in Iraq is due to the positive results it achieves for the segments of society and the guarantee of their rights within a single constitution and through the realization of the principle of political decentralization, which is the distinguishing feature of the principle of federalism that enjoys a kind of flexibility within the concept of union.